Radio as A Tool for Society Empowerment in Sub-Saharan States - Yeremia Nicolaus Widjanarko (Jurnal Hubungan Internasional, 2019)
The rapid development experienced by the mass media has changed theway societies access information. It could be proven by the existence ofcommunication and information technology, which requires variousconditions such as qualified educational experiences, good economicconditions, and the existence of adequate infrastructures. However, theserequirements are not easy to be met by people in sub-Saharan countries.As a result, people in sub-Saharan countries use radio instead as a massmedia to obtain information. Regarding this phenomenon, the authorsees an opportunity to use radio as a tool for community empowerment,precisely through the spread of endemic knowledge. The author thenuses the marginal utilitarianism method with a bottom-up approachexplaining how radio could be used in community empowerment whichresulted into information blending methods. The purpose of the paperitself is to give new insight on ways to empower society, precisely throughthe use of traditional mass media.